Evaluation of the recycling activity in Lima Norte - Huiman Cruz, Alberto (2018)
In order to evaluate the recycling activity of materials in North Lima, the following were applied: (1) surveys, using the probabilistic sampling method with the simple random type for all the actors of the recycling pyramid, and (2) interviews with open and simple type to the authorities and actors of the recycling chain (in the period between January 2015 and December 2016). It was determined that the product that demands the greatest interest of the productive chain of local recycling is plastic for its cost and quantity, the other elements complement recycling. The results allowed to determine who receives the highest income is the exporter PEN 6,850.00, and throughout the recycling chain the local governments of North Lima and the actors of the recycling chain do not develop a joint work by: Resistance of insertion of public policies within the framework of existing regulations, lack of data and information, there is sectoral disorganization, disobedience to authority prevails and supervision, oversight and sanctions are lacking. In conclusion, there is a gap in environmental assessment, mainly in plastic because the participation system in recycling does not depend on economic incentives causing a decrease in the market, the polluter-pays principle is not applied, and there is informality in the development of activity. Therefore, the sustainability of the recycling activity in Lima North will be possible as long as it coexists: Articulation of development.